2019 Physics Education Research Conference Proceedings 2020
DOI: 10.1119/perc.2019.pr.burkholder
|View full text |Cite
|
Sign up to set email alerts
|

Assessing problem-solving in science and engineering programs

Abstract: Science and engineering (S & E) programs frequently claim that they teach undergraduate students how to be good problem solvers. However, there has been little research to-date that demonstrates this, in no small part due to the fact that measuring problem-solving is quite difficult. Our recent work characterized experts' problemsolving as carrying out a series of several dozen decisions made in solving novel problems; these decisions are remarkably consistent across S & E disciplines. Based on this, we develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…An important area of future research is how we can effectively teach our students these expert predictive frameworks. Indeed, some preliminary investigations suggest that standard instructional practices and curriculum are not teaching these frameworks and their application to students in chemical engineering [40] or medicine [39], and our results here show that the same is true in physics courses at Stanford. Because predictive frameworks are mental models of problems' key features and the relationships between them, we suggest that instruction in problem solving should focus on having students identify the key features of given problems, and then practice manipulating the relationships between relevant variables.…”
Section: General Discussion and Conclusionmentioning
confidence: 57%
“…An important area of future research is how we can effectively teach our students these expert predictive frameworks. Indeed, some preliminary investigations suggest that standard instructional practices and curriculum are not teaching these frameworks and their application to students in chemical engineering [40] or medicine [39], and our results here show that the same is true in physics courses at Stanford. Because predictive frameworks are mental models of problems' key features and the relationships between them, we suggest that instruction in problem solving should focus on having students identify the key features of given problems, and then practice manipulating the relationships between relevant variables.…”
Section: General Discussion and Conclusionmentioning
confidence: 57%
“…2. We also coded the responses to two questions for how closely student responses matched expert responses collected previously [19]. We first coded the criteria the students used to evaluate their process and how it matched the criteria listed by experts in the previous study.…”
Section: Methodsmentioning
confidence: 99%
“…Textbook problems are not suited to this task because the expert decisions are often made for the solver-for example, assumptions are almost always given to the solver in physics problems, rather than allowing the solver to identify appropriate assumptions or simplifications. We found that a troubleshooting task, such as critiquing a flawed product design schematic, was well-suited for this assessment, as it requires the solver to make many of the expert decisions [19]. The general structure for the assessment, which may be applied in any science and engineering discipline, is depicted in Fig.…”
Section: Testing An Assessment Of Problem-solving In Introductory Chemical Process Design Courses (Wip)mentioning
confidence: 99%
See 1 more Smart Citation
“…The basic components of the framework are 1) provide an authentic problem context, 2) ask a series of questions that require test-takers to make decisions about problem definition and planning how to solve, 3) provide more information, 4) ask a series of questions that require decisions about interpreting information and drawing conclusions, and 5) have test-takers choose and reflect on their solution. One of the authors has previously developed such an assessment in chemical process design 28 . One important feature of these assessments is that students are not graded based on a scale that compares them to one another, but rather compares their responses to a consensus of experts.…”
Section: Theorymentioning
confidence: 99%